Kinematics and dynamics pf giant stars in the solar neighbourhood - Famaey, Benoît (Universite Libre de Bruxelles, 2004)
We study the motion of giant stars in the Solar neighbourhood and what they tell us about the dynamics of the Galaxy: we thus contribute to the huge project of understanding the structure and evolution of the Galaxy as a whole. We present a kinematic analysis of 5952 K and 739 M giant stars which includes for the first time radial velocity data from an important survey performed with the CORAVEL spectrovelocimeter at the Observatoire de Haute Provence. Parallaxes from the Hipparcos catalogue and proper motions from the Tycho-2 catalogue are also used. A maximum-likelihood method, based on a bayesian approach, is applied to the data, in order to make full use of all the available stars, and to derive the kinematic properties of the subgroups forming a rich small-scale structure in velocity space. Isochrones in the Hertzsprung-Russell diagram reveal a very wide range of ages for stars belonging to these subgroups, which are thus most probably related to the dynamical perturbation by transient spiral waves rather than to cluster remnants. A possible explanation for the presence of young group/clusters in the same area of velocity space is that they have been put there by the spiral wave associated with their formation, while the kinematics of the older stars of our sample has also been disturbed by the same wave. The emerging picture is thus one of "dynamical streams" pervading the Solar neighbourhood and travelling in the Galaxy with a similar spatial velocity. The term "dynamical stream" is more appropriate than the traditional term "supercluster" since it involves stars of different ages, not born at the same place nor at the same time. We then discuss, in the light of our results, the validity of older evaluations of the Solar motion in the Galaxy. We finally argue that dynamical modeling is essential for a better understanding of the physics hiding behind the observed kinematics. An accurate axisymmetric model of the Galaxy is a necessary starting point in order to understand the true effects of non-axisymmetric perturbations such as spiral waves. To establish such a model, we develop new galactic potentials that fit some fundamental parameters of the Milky Way. We also develop new component distribution functions that depend on three analytic integrals of the motion and that can represent realistic stellar disks. === Doctorat en sciences, Spécialisation physique === info:eu-repo/semantics/nonPublished